2008
DOI: 10.1021/jo800483a
|View full text |Cite
|
Sign up to set email alerts
|

A New Cyclization to Fused Pyrazoles Tunable for Pericyclic or Pseudopericyclic Route: An Experimental and Theoretical Study

Abstract: 2-Pyrazinyl (2) and 3-pyridazinylketone arylhydrazones (6) and their benzologues undergo a ring closure reaction to yield pyrazolo[3,4- b]pyrazines (4) and pyrazolo[4,3- c]pyridazines (7), respectively, in acceptable to good yields. The reaction was found to be accelerated by using acidic or basic conditions. Quantum chemical calculations suggest the key step of the mechanism to be a direct cyclization; analysis of aromaticity based on computed magnetic properties revealed its medium-dependent pericyclic or ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Structure 14 was excluded based on 1 H-NMR and 13 C-NMR that revealed the absence of signals for a sp 3 carbon or protons linked to such a carbon ( Scheme 3 ). It can thus be concluded that while compound 1 is a versatile precursor to azolylpyridines, conversion of compound 2 to pyrazolo[4,3- b ]pyridine via a route similar to that reported for converting 8 into 9 could not be effected, at least under the conditions reported in the published work [ 13 ].…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Structure 14 was excluded based on 1 H-NMR and 13 C-NMR that revealed the absence of signals for a sp 3 carbon or protons linked to such a carbon ( Scheme 3 ). It can thus be concluded that while compound 1 is a versatile precursor to azolylpyridines, conversion of compound 2 to pyrazolo[4,3- b ]pyridine via a route similar to that reported for converting 8 into 9 could not be effected, at least under the conditions reported in the published work [ 13 ].…”
Section: Resultsmentioning
confidence: 66%
“…The behavior of 2 towards hydroxylamine is thus similar to that of other hydrazononitriles and differs from that of 2- p -nitrophenyl-2-arylhydrazonoacetonitrile where rearrangement preceded cyclization affording 1,2,4-triazoles 7 . Although 2-arylhydrazono-2-acetylpyridine 8 has been recently reported to afford 9 when heating in dichlorobenzene at 190 °C, in our hands, compounds 2a-c have been recovered unaffected under these conditions [ 13 ]. It seems that replacing a methyl by a cyano group affects the HOMO-LUMO energy of the cyclised 6π electron system as this cyclization is believed to proceed by a pericyclic rule.…”
Section: Resultsmentioning
confidence: 95%
“…In this connection, they developed a simple and effective criterion, namely the NICS, which is the negative of the computed magnetic shielding at or above the ring centers 49–51. This parameter has been used to distinguish between pericyclic and pseudopericyclic mechanisms 52, 76. We determined the NICS values of the transition structures involved in the pericyclic and pseudopericyclic pathways (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In connection with the theoretical investigation of the Diels‐Alder reaction of butadiene and ethylene, Houk and coworkers54 compared different theoretical levels for the calculation of the reaction enthalpies and activation barriers and found that the values obtained by using B3LYP hybrid functional with 6‐31G* basis set were the best and close to the experimental values. Likewise, computations were carried out at B3LYP/6‐31G* level to investigate the mechanism of 1,5‐electrocyclization of azinyl and diazinyl ketone hydrazones to fused pyrazoles 52. Arduengo et al 18–20.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation